Are there Negative Returns to Aid? : A Comment - Nkusu, Mwanza (IMF Working Papers; Working Paper ;, 2004)
Amid controversies surrounding aid effectiveness, an increasing number of empirical studies find support for the idea that aid can spur growth and that the aid-growth relationship is nonlinear. Lensink and White propose a model to illustrate the possible existence of what has been labeled an "aid Laffer curve." This short paper highlights the model's weaknesses and suggests that the model does not fulfill the purpose of illustrating the possible existence of negative returns to aid.